2021
DOI: 10.3390/separations8100173
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosol and Hydroxytyrosol Determination in Extra Virgin Olive Oil with Direct Liquid Electron Ionization-Tandem Mass Spectrometry

Abstract: Extra virgin olive oil (EVOO) is one of the main ingredients of the Mediterranean diet. It is claimed as a functional food for its unique content of health-promoting compounds. Tyrosol (Tyr), Hydroxytyrosol (Htyr), and their phenolic derivatives present in EVOO show beneficial properties, and their identification and quantification, both in their free form and after the hydrolysis of more complex precursors, are important to certify its quality. An alternative method for quantifying free and total Tyr and Htyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
(44 reference statements)
0
10
0
Order By: Relevance
“…Standard EI ion sources were used during solvent elution such as in electron ionization LC-MS systems (EI-LC-MS) by various researchers, including the group led by Cappiello, as evidenced by their publications. , EI provides a few unique benefits for LC-MS in comparison with ESI and APCI such as library-based identification including at the isomer level, ionization of nonpolar compounds, and the elimination of ion suppression effects. Notably, they have also implemented flow-injection analysis directly into the standard EI ion source without LC separation, and ref shares similarities with this paper. However, in contrast to SIRTA with Cold EI, flow injection in EI-LC-MS systems required added hardware.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Standard EI ion sources were used during solvent elution such as in electron ionization LC-MS systems (EI-LC-MS) by various researchers, including the group led by Cappiello, as evidenced by their publications. , EI provides a few unique benefits for LC-MS in comparison with ESI and APCI such as library-based identification including at the isomer level, ionization of nonpolar compounds, and the elimination of ion suppression effects. Notably, they have also implemented flow-injection analysis directly into the standard EI ion source without LC separation, and ref shares similarities with this paper. However, in contrast to SIRTA with Cold EI, flow injection in EI-LC-MS systems required added hardware.…”
Section: Discussionmentioning
confidence: 85%
“…However, in contrast to SIRTA with Cold EI, flow injection in EI-LC-MS systems required added hardware. Furthermore, flow injection with standard EI typically uses a low, sub-μL/min solvent flow rate (0.4 μL/min , ) and thus can experience relatively long void time. We developed and employed electron ionization LC-MS with Cold EI either with separation or in its flow-injection analysis mode .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, these correlations were consistent with previous studies demonstrating the presence of Tyr and/or OHTyr in human or animal urine and plasma after the consumption of the aforementioned foods. Table olives and olive oil are rich sources of Tyr and OHTyr; curiously, whereas in table olives, the amounts of OHTyr are usually higher than Tyr, in olive oil, the opposite occurs [ 26 , 27 ]. Likewise, regardless of the food source, it was observed that OHTyr excretions were usually higher than those of Tyr in urine and plasma [ 13 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated in earlier studies, ACN was preferred as the nonpolar solvent over MeOH due to prior experimental evidence that it is best suited to the LEI interface. 37,38,57 All optimized parameters are listed in section 2.5. The base peaks observed in the scan spectra of PFASs were selected as m/z ions for SIM analysis (Table 2).…”
Section: Acn Flow Ratementioning
confidence: 99%
“…Only a few research articles refer to NCI fragmentation 59,60. The fragmentation was governed by the dissociative electron capture mechanism, primarily resulting in the loss of −CH 3 and −COOH terminal groups, along with consecutive loss of fluorine atoms in the fragments, leading to the formation of double and triple carbon−carbon bonds in negatively charged fragments 57. The subsequent loss of fluorine atoms in the fragments, resulting from the impact of low-energy electrons with the analytes, is responsible for most signals appearing in the mass spectrum.…”
mentioning
confidence: 99%